FLUID FLOW RELATED FEATURES AS AN INDICATOR OF POTENTIAL GAS HYDRATE ZONE: WESTERN CONTINENTAL MARGIN OF INDIA - Shankar U.; Thakur N.K.; Ashalatha B. (My University, 2006)
Multichannel seismic reflection data from the continental margin of western India suggest the potential presence of fluid expulsion features, which may or may not be associated with gas hydrates. No typical bottom simulating reflector was observed on the reflection seismic section. As a result we look for other evidence in seismic sections in a small corridor of the western continental margin of India in order to establish the presence of gas hydrates. We study features including venting through the seafloor, pockmarks, sea floor collapse, faults acting as migration paths for fluid flow, transparent gas-charged sediment, reduction in amplitude strength, diapirism and mud-volcano. Presence of all these gas-escape features on a seismic section implies the probable presence of methane within the zone of hydrate stability field. © Springer Science+Business Media B.V. 2006.
Keywords: BLANKING; BOTTOM-SIMULATING REFLECTOR; GAS HYDRATES; POCKMARKS AND DIAPIRS; VENTING OF GAS; WESTERN CONTINENTAL MARGIN OF INDIA